A Mouse Intra-Intestinal Infusion Model and its Application to the Study of Nanoparticle Distribution - Sadio, Ana; Amaral, Ana L.; Nunes, Rute; Ricardo, Sara; Sarmento, Bruno; Almeida, Raquel; Tsukamoto, Hidekazu; das Neves, José (Frontiers in Physiology, 2016)
The oral route is the most preferable one when it comes to drug administration. Different animal models have been used to characterize the fate of potential medicines upon oral delivery but fail to clarify specific events occurring at localized sites of the gastrointestinal tract, particularly at the small intestine. We developed a new mouse intra-intestinal infusion model that enabled the direct administration of substances (such as drugs or nanoparticle drug carriers) in the small intestine through an implanted catheter, which can be maintained for prolonged periods of time. The location of catheter insertion can be previously determined as more proximal or distal, allowing to test specific portions of the intestine. Since the model is able to presumably maintain normal physiological characteristics, namely the mucus coating of the intestinal wall, it allowed studying the distribution of different nanoparticles upon localized intra-intestinal administration. The hereby proposed mouse model has the potential to be useful in other types of studies, namely in clarifying localized processes occurring at specific sites of the intestine.